On the temperature dependences of thermoelectric characteristics of thermoelectric material-metal transient layer without regard to percolation effect - Gorsky , P.V.; Mytskaniuk, N.V. (Journal of Thermoelectricity, 2019)
The basic relationships are obtained by calculation, which determine the temperature dependences of thermoelectric characteristics of thermoelectric material-metal transient contact layers without regard to percolation theory. Specific quantitative results and plots of the temperature dependences of the electrical and thermal contact resistances, the thermoEMF, the power factor, and the dimensionless thermoelectric figure of merit are given for bismuth telluride – nickel contact pair. It has been established that with uneven distribution of metal atoms in the temperature range of 200 - 400 K, the intensity of metal atoms entering transient layer, which corresponds to a change in the distribution of metal atoms by the thickness of transient layer from linear to square and the thickness range of transient layer from 20 to 150 µm, the electrical contact resistance varies from 1.8 · 10-7 to 4.8 · 10-6 Оhm·сm2, the thermal contact resistance - from 0.022 to 0.35 K·сm2/W, the thermoEMF - from 155 to 235 μV/K, the power factor - from 1.6·10-4 до 2.9·10-4 W/(m·K2), the dimensionless thermoelectric figure of merit - from 0.55 to 1.7. Bibl. 34, Fig. 21.